Advances and limits of low-carbon mobility policies in the city of São Paulo - Jaqueline Nichi; Gabriela Marques Di Giulio; Fabiana Barbi Seleguim; Leila da Costa Ferreira (Ambiente & Sociedade)
Abstract This article analyses the advances and limitations of political urban planning instruments at the municipal level to address climate impacts on mobility. The study focuses on the specific regulatory instruments of the city of São Paulo, such as the Municipal Climate Change Policy (PMMC), the Urban Mobility Plan (PlanMob SP), the Strategic Master Plan (PDE), and the Climate Action Plan (PlanClima SP). These policies regulate adaptive measures through planning, mobility management and land use in the municipality. The analysis reveals that São Paulo has relevant planning instruments that include solutions to the climate crisis in urban transport, but that still require adjustments to incorporate new modes and technologies with the potential to decarbonize the sector. Among the main challenges identified, economic and regulatory limitations to boost the use of technology stand out, including the taxation of new modes, the expansion of the fleet of more sustainable vehicles and the adoption of biofuels.